On q-Sumudu Transforms of Certain q-Polynomials - (:unkn) unknown (UNIV NIS, FAC SCI MATH, 2013)
Although Sumudu transform is the theoritical dual of the Laplace transform, it has many applications in sciences and engineering for its special fundamental properties. In a previous paper [3], we studied q-analogues of the Sumudu transform and derived some fundamental properties. This paper follows the previous paper and aims to provide some applications of the q-Sumudu transform. The authors give q-Sumudu transforms of some q-polynomials and q-functions. Also, we evaluated the q-Sumudu transform of basic analogue of Fox's H-function.
Keywords: q-Sumudu transforms; q-Hypergeometric functions; q-special polynomials; Fox's H-function